Some Comments on the Development of Reading in the Internal Affairs Bodies of the Republic of Uzbekistan (In the Case of the Mia of Fergana Region) - Temirova Mashhura Muhammadaminovna; Mirzaliyeva Zarina Jahangirovna (Genius Publishing Group, 2022)
The article in the organs of internal affairs of the republic of Uzbekistan concerning the development of bilateral relations review some of the readers in the example of Fergana region police office was the analysis. Additionally, the article in fergana region police office in the city and district of the republic of uzbekistan ministry of internal affairs of the 400 year 2021 October 21-number of command for the execution of works was the discussion of results
Keywords: Internal affairs; number; uzbekistan; results